Temperature Changes Inside the Kidney: What Happens During Holmium:Yttrium-Aluminium-Garnet Laser Usage? - ŞENER, TARIK EMRE (MARY ANN LIEBERT, INC, 2016)
Introduction: The improvements in flexible ureteroscopes provide efficient access to the upper urinary tract and advancements in laser technology strengthens the endourologists' armamentarium. The endourologists must be aware of the advantages and the potential complications of these powerful technological equipments. Our aim is to demonstrate temperature evolution during laser use inside an artificial kidney model. Materials and Methods: We created a bench model using K-Box((R)) immersed into a saline-filled heating tank, which was used to obtain the needed temperature inside the cavity to provide different real-time situations. An endotracheal thermometer was placed inside. We used Olympus URF-P6 ureteroscope and Rocamed Holmium:yttrium-aluminium-garnet laser with two different fibers; 200 and 272m, at five different settings. Irrigation at room (24.5 degrees C) and body (36.5 degrees C) temperatures was used. We measured temperatures at 15th, 30th, and 45th seconds and 1st, 2nd, and 5th minutes of laser use with and without irrigation. We stopped measurements when temperature reached the upper limit of the endotracheal thermometer. Results: When irrigation was closed, with 272-m laser fiber, we reached the temperature limit more rapidly with saline tank at 36.5 degrees C than the tank at 24.5 degrees C. When irrigation was closed, with both fibers and regardless of tank temperature and laser settings, the system surpassed the maximum temperature limit. With 272-m laser fiber, the limit was reached as early as the 30th second. When the irrigation was open, we did not reach the maximum temperature limit regardless of tank temperature and laser setting. When two laser fibers were compared, the temperature increase was more pronounced with 272-m fiber, but the difference was not statistically significant. Conclusion: Laser use during flexible ureteroscopy may cause increased intrarenal temperatures. Rapid increases should be kept in mind when irrigation is closed. The irrigation seems to limit the temperature increase when used with any laser setting.
Keywords: YAG LASER; FLEXIBLE URETERORENOSCOPY; PROTEIN DENATURATION; FIBER DIAMETERS; URETEROSCOPY; LITHOTRIPSY; UROLOGY; THERMOTOLERANCE; FRAGMENTATION; TECHNOLOGIES